HIV infection and the Turkish people: A cross-sectional study on the perceptions of safranbolu inhabitants - (:unkn) unknown (Acta Medica Mediterranea, 2013)
Objective: Knowledge and attitudes about HIV/AIDS were examined in a Muslim population living in the Safranbolu District of Turkey. Materials and methods: The survey was conducted over 431 participants in December 2011.A questionnaire, consisting of 47 questions, was used to measure the level of participants' knowledge and attitudes about HIV. Results: The findings indicated that the participants have sufficient knowledge of HIV and present positive attitudes toward persons living with HIV (PLWH). Nevertheless, 84% of participants stated that they would not sit in the same armchair with a PLWH, 60.3% that they would not kiss a PLWH. Mass media was the main source of information. More than half of the participants also stated their desire to learn more about HIV. Conclusions: Participants' levels of knowledge about HIV did not match their behaviors and attitudes about HIV. Due tothis, education strategies to enhance knowledge levels and to develop positive attitudes toward PLWH should be employed.
Keywords: AIDS; Attitude; HIV; Knowledge; Turkey